2013
DOI: 10.1016/j.jtcvs.2012.07.087
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle training for diaphragm dysfunction after cardiac surgery

Abstract: Inspiratory muscle training may improve inspiratory muscle strength and increases paralyzed diaphragm mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 25 publications
2
47
0
3
Order By: Relevance
“…In fact, inspiratory muscle training (IMT) may increase diaphragm strength and tone in different clinical settings (2,16). There is some evidence that prolonged inspiratory effort can improve gastroesophageal reflux.…”
mentioning
confidence: 99%
“…In fact, inspiratory muscle training (IMT) may increase diaphragm strength and tone in different clinical settings (2,16). There is some evidence that prolonged inspiratory effort can improve gastroesophageal reflux.…”
mentioning
confidence: 99%
“…These complications increase morbidity and mortality rates, slowing down the recovery process in patients [2]. In the 20 years of our clinic practice of cardiology, we have frequently encountered a plegia of the phrenic nerve, that may be transient, partially permanent or permanent, as found in published literature [2,3]. The lesion of the phrenic nerve may occur in 60% -85% of the population undergoing thoracic cardiac surgery, in particular the left nerve [3,4].…”
Section: Objectivesmentioning
confidence: 99%
“…[5] Respiratory muscles are affected after cardiac surgeries. It has been shown that domiciliary program of inspiratory muscle training was safe and improved the forced vital capacity and the maximum voluntary ventilation, although the clinical benefits of this program were not clearly [8][9][10]2017 demonstrable. [6] Postoperative pulmonary complications (PPCs) after coronary artery bypass graft (CABG) surgery are a major source of morbidity and mortality, and increase length of hospital stay and resource utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Inspiratory muscle training may improve inspiratory muscle strength and increases paralyzed diaphragm mobility. [10] Most patients are readily liberated from mechanical ventilation (MV) support, however, 10% -15% of patients experience failure to wean (FTW). FTW patients account for approximately 40% of all MV days and have significantly worse clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%